The Role of the Government Regulation in Online Transportation: A Model Validation - Ambarwati, Okki Chandra; Nugroho, Rino Ardhian; Suharto, Didik Gunawan (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2019)
The online transportation has been a concern in many countries. It caused social problems with more established conventional transportation such as taxis and buses. Some countries had issued policy to regulate online transportation, while some others did not. Indonesia is facing the similar dilemmas. On one hand online transportation provides new jobs but on the other hand it adds congestion and creating threats to the conventional public transportation presence. This research is conducted to reveal the public opinion towards the continued use of online transportation. The insight of this issue might help government in deciding whether or not they are issuing a policy on online transportation. To do the research, this study used an information system (IS) model to understand the context of continuance. As the practice of IS model use in public administration research is still very limited this study will focus on the validity of IS model to be used in public administration area. Questionnaire was given to 64 respondents that were chosen using convenient sampling approach. The items of the questionnaire were built based on the well-known IS continuance model with some addition to the predictor variables. The result indicates that IS model could be used in the public administration research as most of the items in the constructs were valid and reliable. Another important finding is that government regulation is the valid predictor of public intention to reuse online transportation. This study suggests government to issue a policy to regulate online transportation, by having a balance portion on maintaining economic growth and providing social stability. Further suggestions are discussed in the paper.